Measuring Activity of Native Plant Sirtuins - The Wheat Mitochondrial Model - Soccio, Mario; Laus, Maura N.; Alfarano, Michela; Pastore, Donato (Frontiers in Plant Science, 2018)
Sirtuins are NAD+-dependent deacetylase enzymes that have gained considerable interest in mammals for their recognized importance in gene silencing and expression and in cell metabolism. Conversely, knowledge about plant sirtuins remains limited, although a sirtuin-mediated regulation of mitochondrial energy metabolism has been recently reported in Arabidopsis. However, so far, no information is available about direct measurement of intracellular plant sirtuin activity, i.e. in cell extracts and/or subcellular organelles. In this study, a novel approach was proposed for reliable evaluation of native sirtuin activity in plant samples, based on i) an adequate combinatory application of enzymatic assays very different for chemical basis and rationale and ii) a comparative measurement of activity of a recombinant sirtuin isoform. In particular, two sirtuin assays were applied, based on bioluminescence emission and Homogeneous Time-Resolved Fluorescence (HTRF®) technology, and the human SIRT1 isoform (hSIRT1) was used for comparison. For the first time in plants, this new approach allowed measuring directly a high and nicotinamide-sensitive sirtuin activity in highly purified mitochondrial fraction obtained from durum wheat (WM). WM-sirtuin activity was 268±10 mU∙mg-1 protein, as measured by HTRF® assay, and 166±12 ng hSIRT1 eq.∙mg-1 protein, as evaluated by the bioluminescent assay and calculated on the basis of the hSIRT1 calibration curve. Moreover, effects of resveratrol and quercetin, reported as potent hSIRT1 activators, but whose activation mechanism is still debated, were also studied. No effect of resveratrol was found on both WM-sirtuin and hSIRT1 activities, while only a slight increase, up to about 20%, of hSIRT1 activity by quercetin was observed. In the whole, results of this study indicate that WM may represent a good system for studying native plant sirtuins. In fact, the high yield of purified WM and their high sirtuin activity, together with use of microplate readers, allow performing a large number of measurements from the same preparation, so qualifying the approach for application to large-scale high-throughput screening. Moreover, WM may also represent an excellent tool to investigate physiological role and modulation of plant sirtuins under experimental conditions more physiologically relevant with respect to recombinant purified enzymes.